SISTEM INFORMASI KEUANGAN PRODUKSI SAWIT PADA PT. MENDALO PRIMA INTILAND (MPI): Salary Data;Harvest Data;Data Processing;Production;Information Systems;Web. - simorangkir, lucy; Anggaraini, Puja (JURNAL AKADEMIKA, 2021)
Along with the increasing needs of companies in managing and processing data for increasingly complex operational activities at this time, of course a data processing and management system is needed that has a high level of effectiveness and efficiency. The purpose of this research is to build a Financial Information System for Palm Oil Production at PT. Mendalo Prima Intiland (MPI). With input requirements from the information system, namely admin data, harvesting employee data, position data, attendance data, harvest data, revenue data, and expenditure data. The form of the process carried out by the system to display the desired results in making process requirements information includes the login process, main menu display, harvesting employee data menu display, position menu display, attendance menu display, harvest menu display, salary menu data display, menu data display receipts and disbursements, as well as the supervisor menu display.The output requirements generated are in the form of information and reports that will be displayed in the form of harvest data reports, attendance data, salary data and salary slip data. This Financial Information System is a way to facilitate office administration in processing data, the expected results of a web-based information system using PHP and MySQL can fix all the shortcomings that exist in the old system.